Effect of bulge shape on wrinkling formation and strength of stainless steel thin sheet - Hassan, Mohamed Mohsen Abdel-Naeim; Saleh, M.A.E.; Takakura, Norio; Ramesh, Singh; Purbolaksono, Judha (Elsevier, 2012)
Embossing and restoration is a simple method to increase the strength of thin sheet metals by creating concentric pattern of wrinkles onto thin sheet-metal plates. SUS304 stainless steel sheets of 0.4 mm thickness were experimentally bulged using hemispherical punches, and then compressed between two flat platens of a testing machine to produce the wrinkles. The process simulation was carried out using finite element method to investigate the effect of bulge shape and height on the wrinkling formation and sheet strength. Thickening of the plate was observed during the compression step and after the thinning that is occurred during the bulging step. Different restoration patterns were observed as bulge height increases. Also, the number of wrinkles within a pattern and its distribution throughout the plate were depending upon the bulged shape. The pressure bearing capacity of the compressed part rapidly accelerates with the increase of wrinkles inclusion. Virtual deflection tests were carried also out using the finite element method (FEM) to evaluate the effect of the wrinkles pattern on the thin plate rigidity or strength. The results showed that the technique is effective in enhancing the strength, the flexural deflection and reducing the failure risk of thin sheet metals parts. This can contribute in the weight reduction of sheet metal parts. The observed patterns can be utilized in sheet decoration. (c) 2012 Elsevier Ltd. All rights reserved.